South African audiologists need business skills to survive: toward a responsive curriculum - Sebothoma, Ben; Khoza-Shangase, Katijah; Moroe, Nomfundo (Frontiers in Education, 2025)
South African audiologists are struggling to find jobs after completing their compulsory government-mandated year of community service in public healthcare institutions. This is in spite of the documented inequity in audiology service provision, and capacity versus demand challenges around the ear and hearing workforce in the presence of an increasing prevalence of hearing and vestibular disorders. The high prevalence of hearing and vestibular disorders linked to various causes including the quadruple burden of disease that South Africa suffers from indicates that there is a clear need for more audiologists to be employed in various sectors in order to improve access to hearing healthcare and enhance early identification and intervention to reap the economic and quality of life benefits of preventive care. We argue for urgent curriculum reform that is responsive to the context by equipping South African audiology students with the skills to be able to successfully confront the current economic crisis.